2020
DOI: 10.1080/13669877.2020.1800066
|View full text |Cite
|
Sign up to set email alerts
|

Amplification without the event: the rise of the flexitarian

Abstract: The social amplification of risk framework typically represents consequential effects associated with high levels of media attention proceeding from an initial risk event. This study considers selective meat-eating as risk-related social behaviour that is evidently not initiated by a single event yet, nevertheless, is demonstrably subject to extensive and broadbased media coverage. Recent reported trends indicate a rise in socalled 'flexitarianism' and reducetarianism' whereby people choose to restrict their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
4
7
0
Order By: Relevance
“…For example, Participant 02 said: “I have tried to eat slightly healthier meals for dinner as opposed to simply the quick and easy option. I certainly have tried to eat less meat,” and Participant 08 said: “So, we're actually only allowing ourselves to have two meat days, and then we try to have two fish days and a vegetarian day Monday to Friday.” This is consistent with Duckett et al (2020) , who found that self-imposed restrictions on meat consumption range from choosing a meat-free day of the week or month to a more general pattern of occasional meat-eating. Participant 24 said they and their partner had made the conscious decision to buy less beef since homeworking: “We don't buy beef at all anymore.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…For example, Participant 02 said: “I have tried to eat slightly healthier meals for dinner as opposed to simply the quick and easy option. I certainly have tried to eat less meat,” and Participant 08 said: “So, we're actually only allowing ourselves to have two meat days, and then we try to have two fish days and a vegetarian day Monday to Friday.” This is consistent with Duckett et al (2020) , who found that self-imposed restrictions on meat consumption range from choosing a meat-free day of the week or month to a more general pattern of occasional meat-eating. Participant 24 said they and their partner had made the conscious decision to buy less beef since homeworking: “We don't buy beef at all anymore.…”
Section: Resultssupporting
confidence: 90%
“…A range of individual-level factors (such as lifestyle, preferences, gender) influence the choice to consume meat ( Rosenfeld & Tomiyama, 2020 ; Tobler et al, 2011 ). Environmental concerns, health considerations and animal welfare issues are examples of individual-level factors associated with decisions to eat less meat ( Duckett et al, 2020 ). These can change over time and place but are unlikely to change in isolation ( Kemper, 2020 ).…”
Section: Conceptualising Influences On Food Choicesmentioning
confidence: 99%
“…These two factors together correspond to 56% of all the motivations that guided our participants' choices, followed by individual health concerns (33%). Similar findings have been found by Duckett, Lorenzo-Arribas, Horgan, and Conniff [30] and Kemper & White [26], who analyzed the motivations associated with adherence to flexitarianism and identified that they include (i) awareness of the environmental impacts of meat consumption; (ii) individual health concerns; and (iii) animal welfare concerns. Other studies [29,31,32,33,34] also confirm these factors.…”
Section: Discussionsupporting
confidence: 81%
“…ii This tri-fold classification of flexitarian motivations finds further support in a recent study which uses flexitarianism, as reported in the national print news media, to explore the theory of the social amplification of risk (Duckett et al 2020) and offer a different, sociological perspective to the other work cited here.…”
supporting
confidence: 58%